Nilai-Nilai Sosial Pada Tradisi Kesenian Jaranan Di Desa Bukit Makmur Kecamatan Pinang Raya Kabupaten Bengkulu Utara - Gita Arra Hervina; Ismail; Sepri Yunarman (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
The primary objective of this research is to identify the social values ​​embedded in the Jaranan art tradition in Bukit Makmur Village, Pinang Raya District, North Bengkulu Regency. Accordingly, the research focuses on uncovering and gaining a deeper understanding of the social values ​​within the Jaranan art tradition. The author uses a qualitative research method. The researcher collects information through interviews, observations, and documentation. Based on this study, there are three different but interrelated phases in the Jaranan art heritage in Bukit Makmur Village, namely: pre-performance rituals, the performance itself, and post-performance briefings. Social values ​​such as commitment, kinship, empathy, tolerance, loyalty, and discipline are embedded in this tradition. Meanwhile, humanitarian values ​​include religious principles, as seen in rituals such as prayer and worship, and ethical principles, including kindness, responsibility, and respect for one another. The younger generation, village council, school system, and community all play an active role in preserving Jaranan art in this hamlet. In addition to the role of community culture, the function of education in cultural socialization through schools is also important, and the role of the village government in providing facilities and including jaranan in official events is also significant. However, as a result of modernization, the involvement of young people is still considered low. The involvement of educational institutions, support from local governments, and strong community involvement are the driving forces behind this practice. Therefore, this study recommends the need to strengthen synergy between educational institutions, local governments, and the community in efforts to preserve the Jaranan art tradition, as well as increasing development and socialization programs for the younger generation so that the social values ​​contained therein are maintained and sustainable